The Effect of Extracorporeal Shock Wave Therapy in the Treatment of Patients with Trigger Finger - Vahdatpour B; Momeni F; Tahmasebi A; Taheri P (Dove Medical Press, 2020)
Babak Vahdatpour, Fahimeh Momeni, Ali Tahmasebi, Parisa Taheri Department of Physical Medicine and Rehabilitation, Isfahan University of Medical Sciences, Isfahan, IranCorrespondence: Parisa TaheriIsfahan University of Medical Sciences, School of Medicine, Department of Physical Medicine and Rehabilitation, Hezar-Jarib Avenue, Isfahan, IranEmail Prs_taheri@yahoo.comIntroduction: Trigger finger disorder is a sudden release or locking of a finger during flexion or extension. Regarding the complications and disadvantages mentioned for the methods used in the treatment of trigger finger disorder, the aim of this study was to investigate the effect of extracorporeal shock wave therapy in the treatment of patients with trigger finger.Methods: This study was an interventional study recruiting 19 patients with trigger finger disorder. Evaluation of pain severity, severity of triggering, and functional impact of triggering was carried out using the Visual Analogue Scale, Trigger Finger Score suggested by Quinnell, and Quick-Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire, respectively, before intervention, immediately after intervention, and in 6 and 18 weeks after intervention. Each patient was treated with extracorporeal shock wave therapy in three sessions with a 1-week interval. Data were analyzed in Statistical Package for the Social Sciences (SPSS) software using ANOVA to monitor changes in pain severity, severity of triggering, and functional impact of triggering during follow-ups.Results: There were statistically significant differences with regard to reduction of the pain severity, severity of triggering, and functional impact of triggering before intervention, immediately after intervention, and in 6 and 18weeks after intervention (P< 0.01). However, the effect of extracorporeal shock wave therapy on reducing severity of triggering immediately after intervention did not yield a statistically significant difference compared to before intervention (P> 0.01).Conclusion: It seems that extracorporeal shock wave therapy leads to a reduction in pain severity, severity of triggering, and functional impact of triggering. These effects persisted until the 18th week after the intervention. It is recommended to use extracorporeal shock wave therapy in terms of a non-invasive intervention with no significant complications for patients with trigger finger.Keywords: extracorporeal shock wave therapy, trigger finger, pain severity, severity of triggering, functional impact of triggering